Sonnambule e giovani ribelli: il positivismo italiano nello specchio della letteratura scapigliata - Iacarella, Andreas (Il sogno della farfalla, 2021)
The aim of this article is to describe the critical and problematic relation between Scapigliatura narrative and the Italian positivism. In the work of some authors belonging to this movement (in particular I. U. Tarchetti and A. Boito) it is possible to identify ideas revealing a deep ability to analyze the major flaws and shortcomings of the nascent modernity (theme of the double, psychic influence, difficult fusion between body and mind) as well as between reason and non-conscious. Considered in these terms and under the light of the studies on the eighteen century carried out by C. Gallini, the Scapigliatura can be interpreted as a modern and non conservative attempt of cultural opposition against the dominant positivism.